Environmental phenol associations with ultrasound and delivery measures of fetal growth. (March 2018) - Ferguson, Kelly K.; Meeker, John D.; Cantonwine, David E.; Mukherjee, Bhramar; Pace, Gerry G.; Weller, David; McElrath, Thomas F.
Abstract: Environmental phenols are used commonly in personal care products and exposure is widespread in pregnant women. In this study, we sought to assess the association between maternal urinary phenol concentrations in pregnancy and fetal growth. The study population included 476 mothers who participated in the prospective LIFECODES birth cohort between 2006 and 2008 at Brigham and Women's Hospital in Boston, Massachusetts, USA. Dichlorophenols (DCPs), benzophenone-3, parabens, triclosan, triclocarban, and bisphenol-S were measured in urine from three time points during pregnancy and averaged. Outcome measures were all standardized to create gestational-age specific z-scores and included: 1) birth weight; 2) ultrasound parameters measured at up to two time points in pregnancy (head and abdominal circumference and femur length); and 3) ultrasound estimates of fetal weight from two time points in combination with birth weight. Models were stratified to investigate sex differences. Inverse associations were observed between average 2, 4- and 2, 5-DCP concentrations and birth weight z-scores in males. For example, an interquartile range difference in 2, 4-DCP was associated with a 0.18 standard deviation decrease in birth weight z-score (95% confidence interval [CI] = − 0.33, − 0.02). These associations were observed in models that included repeated ultrasound estimates of fetal weight during gestation as well. Also in males, we noted inverse associations between average triclosan exposure over pregnancy and estimated fetal weight combined with birth weight in repeated measures models. For females, associations were generally null. However, mothers with a detectable concentration of bisphenol-S at any of the study visits had lower weight females. In conclusion, we observed inverse associations between indicators of maternal phenol exposure during pregnancy and fetal growth, with several differences observed by sex. Highlights: Phenols from three visits were averaged to examine associations with fetal growth. We examined birth weight on 476 newborns as well as ultrasound parameters. Dichlorophenols were associated with reduced growth in boys. Detection of bisphenol-S in pregnancy was associated with reduced growth in girls.